Moyamoya Disease: Acute presentation with fever and fits in a 5-Year-Old Female Patient: A Case Report - Saad, Muhammad; Yaseen, Aimen; Shafiq, Faiqa (Biological and Clinical Sciences Research Journal, 2025)
Moyamoya disease is a rare cerebrovascular disorder characterised by the narrowing or blockage of the carotid artery, leading to reduced blood flow to the brain. I present the case of a 5-year-old female patient who experienced recurrent strokes and was diagnosed with Moyamoya disease. The patient exhibited a complex clinical course involving episodes of stroke, fever, and seizures. Detailed examinations, diagnostic tests, and medical interventions were conducted to manage her condition. This case underscores the importance of recognising Moyamoya disease in pediatric patients presenting with recurrent strokes and highlights the challenges associated with its diagnosis and management.